2016
DOI: 10.1002/cctc.201600368
|View full text |Cite
|
Sign up to set email alerts
|

Microkinetic Modeling of Benzyl Alcohol Oxidation on Carbon‐Supported Palladium Nanoparticles

Abstract: Six products are formed from benzyl alcohol oxidation over Pd nanoparticles using O2 as the oxidant: benzaldehyde, toluene, benzyl ether, benzene, benzoic acid, and benzyl benzoate. Three experimental parameters were varied here: alcohol concentration, oxygen concentration, and temperature. Microkinetic modeling using a mechanism published recently with surface intermediates was able to produce all 18 trends observed experimentally with mostly quantitative agreement. Approximate analytical equations derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 92 publications
4
33
0
1
Order By: Relevance
“…For example, for an alcohol/metal ratio of 500 mol/mol the resulting TOF is 1000 h −1 , 1100 h −1 , 700 h −1 and 700 h −1 for a BA concentration of 0.15 M, 0.30 M, 0.60 M and 1 M, respectively. The above results suggests that the surface is largely covered with adsorbates during reaction, which is consistent with the kinetic simulations in reference, where simulations suggested that adsorbed oxygen was the dominant species under most conditions [95].…”
Section: Concentrationsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, for an alcohol/metal ratio of 500 mol/mol the resulting TOF is 1000 h −1 , 1100 h −1 , 700 h −1 and 700 h −1 for a BA concentration of 0.15 M, 0.30 M, 0.60 M and 1 M, respectively. The above results suggests that the surface is largely covered with adsorbates during reaction, which is consistent with the kinetic simulations in reference, where simulations suggested that adsorbed oxygen was the dominant species under most conditions [95].…”
Section: Concentrationsupporting
confidence: 91%
“…Until recently, there was no published mechanism detailed enough for microkinetic modeling. However, Savara et al published a sufficiently complete mechanism and microkinetic model for benzylic alcohol oxidation over Pd/AC and AuPd/AC, [53,86,95] followed by a kinetic study by Galvanin et al [89].…”
Section: Mechanism and Microkinetic Modelsmentioning
confidence: 99%
“…We previously used microkinetic modeling (simulation+fitting) to validate and understand the mechanism for benzyl alcohol oxidation to various products (e.g., benzaldehyde, toluene, benzoic acid, etc.) over Pd/C . Herein, we apply the same microkinetic model based on the mechanism in Scheme to understand the differences in benzyl alcohol oxidation over AuPd/C relative to that over Pd/C and then use density functional theory calculations to validate the differences in the oxygen adsorption properties inferred from the microkinetic modeling.…”
Section: Methodsmentioning
confidence: 99%
“…The temperature and concentration conditions were the same as those in our previous study (Table S1, Supporting Information), and the same microkinetic model was also used (Table S2). The AuPd/C catalyst was prepared by following a two‐step procedure to produce homogenous‐alloyed AuPd nanoparticles .…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, Au nano particle based catalysts were reported to exhibit effective oxidation property for this reaction [14][15][16]. Very recently, carbon supported Pd nano particles are also reported as low temperature active oxidation catalysts for this reaction [17,18]. The simple non-transitional metal based Mg 3 (PO4) 2 catalyst exhibiting promising oxidation property in solvent less conditions make the present study interesting.…”
Section: Accepted Manuscriptmentioning
confidence: 77%